Epstein-Barr virus-associated lymphoproliferative disorders - Ewelina Grywalska; Justyna Markowicz; Piotr Grabarczyk; Marcin Pasiarski; Jacek Roliński (2013)
The Epstein-Barr virus (EBV) is one of the most common human viruses, infecting more than 90% of the world's adult population. In some individuals the interplay between EBV replication, latency and immune control can be disrupted and evokes prolonged proliferation of EBV-infected lymphocytes and their malignant transformation. Since its discovery as the first human tumor virus, EBV has been implicated in the development of a wide range of human cancers. The evidence for an association with EBV is the strongest for Burkitt's lymphoma, NK/T cell lymphoma, nasopharyngeal carcinoma, Hodgkin's lymphoma and for malignant lymphomas in immune incompetent patients. Additionally, certain epithelial cell tumors, such as gastric carcinoma and breast carcinoma, have been defined as EBV related. However, the virus may be encountered in other types of malignancies. The oncogenic potential of EBV is related to its ability to infect and transform B lymphocytes into continuously growing lymphoblastoid cell lines. EBV encodes a series of products mimicking several growth, transcription and anti-apoptotic factors, to usurp control of the pathways that regulate diverse homeostatic cellular functions. However, the exact mechanism by which EBV promotes oncogenesis remains unclear. The focus of this review is to summarize the current knowledge of oncogenic potential of the Epstein-Barr virus and its role in the pathogenesis of EBV-associated lymphoproliferative disorders.